Design of a Slotted Waveguide Antenna by Means of VBScript Scripting Language Macros in CAD Ansys HFSS - V. G. Koshkid’ko; M. M. Migalin (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Modern antenna devices contain a large number of repeating elements. The process of development of CAD models of such devices requires repeatedly performed operations that is a routine task for an engineer. Therefore, the problem of repeating operations automation arises when constructing antenna models with periodic structures.Aim. To demonstrate the automation of slotted waveguide antennas design process in CAD Ansys HFSS.Materials and methods. In order to determine the dimensions of the slotted waveguide antenna the energy method was used. Automation procedure of the design of the slotted waveguide antennas in CAD Ansys HFSS using the Visual Basic Scripting Edition macros was presented.Results. In order to design and edit slotted waveguide antennas in CAD Ansys HFSS four macros in the VBScript language were established: for slot subtraction from a broad wall of a rectangular waveguide at given coordinates; for removing the original slots created using the previous macro; for drawing a polyline passing through the centers of the slots, in order to verify the antenna’s near field realized distribution; for inclined slot subtraction from a narrow wall of a rectangular waveguide at given coordinates. Results of the macros usage were presented.Conclusion. The above mentioned macros allow one to automate the routine steps during the process of creating and deleting objects while designing an antenna model with periodic structures in CAD Ansys HFSS. Specified procedures for creating macros could be extended to a wide class of tasks related to the studies of characteristics of electromagnetic structures including repeating objects (phased antenna arrays, reflective arrays, slotted waveguide antennas, fractal antennas, log-periodic antennas, multi-layer lens antennas, ladder-type microwave filters).